The Palestinian Refugee Regime: Tensions between the Collective Right of Return and Individual Rights - Abdulsamad, Shatha Oqab (AUC Knowledge Fountain, 2021)
Since their initial displacement in 1948, the United Nations had devised a special temporary refugee regime for Palestinians, distinct from the international refugee regime. The distinct regime was structured in order to acknowledge Palestinian displacement as a result of a deliberate policy of state building by Israel as a national home for Jewish people in Palestine, as well as the effect of the United Nations Partition Plan. Premised as different from other refugee problems, the distinct regime devised for Palestinians was intended to be temporary, pending a final settlement that ensures their repatriation. The temporality and structure of the distinct regime were informed by international expertise at the time and the interwar approach to resolving other refugee crises. With time and with no prospect of a solution in sight, Palestinian displacement became more and more conceptualized as a problem of refugees, giving rise to the inability of the distinct regime to speak effectively to their changing needs. This thesis argues that engaging with displaced Palestinians as an expression of a political problem has contributed to the precarity of their protracted situation. The thesis argues that the demise of one of the legs of the distinctive regime, UNCCP, the precarity of the legal status and inconsistent treatment of displaced Palestinians in their host states and the protection gap they experience in the context of secondary forced displacement are tensions and anxieties that signify the inability of the distinctive regime to provide effective protection, further compounding their plight. The thesis stresses the need for the distinct regime to evolve in a direction that offers a higher level of protection for displaced Palestinians in light of their protracted situation. It examines and investigates the major contentions in the area of expanding protection for displaced Palestinians, as well as the tensions between the different forms of protection that these contentions reference. The thesis argues that each of these contentions has its own merits and limitations. Finally, the thesis argues that in light of the protracted displacement of Palestinians, the need to implement a rights-based approach to durable solutions and the protection of their individual rights without jeopardizing the right to the UN-sanctioned durable solutions devised for their plight is rather heightened.